Identification of areas of diversity and distribution of Pongamia based on altitude and seed traits - SUNIL, N; KUMAR, VINOD; SIVARAJ, N; ABRAHAM, BABU; PANWAR, N S; VARAPRASAD, K S (The Indian Journal of Agricultural Sciences, 2012)
A total of 123 germplasm accessions of Pongamia pinnata were collected from peninsular India. Majority, i e 64 accessions (52%) were collected from an altitudinal gradient of 0 to 250 m with oil content ranging from 15.0 to 46.0% and only 0.8% of accessions collected from altitude more than 1 000 m have exhibited modest oil percent of 27.7%. Using DIVA-GIS software, grid maps indicating diversity for oil content and 100- seed weight were generated for these accessions. Highly variant lines for oil content were observed in Prakasam and Srikakulam districts of Andhra Pradesh. However, high diversity index for 100-seed weight was observed in Srikakulam and Chittoor districts of Andhra Pradesh. Rayagad district of Odisha was a potential region for diverse lines of Pongamia germplasm for various seed traits including oil content. High regions of diversity within the surveyed districts have been identified. The present study enabled us to find out suitable altitudinal gradient and diversity rich pockets from Peninsular India.